Increased Expression of Viral Sensor MDA5 in Pancreatic Islets and in Hormone-Negative Endocrine Cells in Recent Onset Type 1 Diabetic Donors - Nigi, Laura; Brusco, Noemi; Grieco, Giuseppina E.; Fignani, Daniela; Licata, Giada; Formichi, Caterina; Aiello, Elena; Marselli, Lorella; Marchetti, Piero; Krogvold, Lars; Jorgensen, Knut Dahl; Sebastiani, Guido; et al. (Frontiers in Immunology, 2022)
The interaction between genetic and environmental factors determines the development of type 1 diabetes (T1D). Some viruses are capable of infecting and damaging pancreatic β-cells, whose antiviral response could be modulated by specific viral RNA receptors and sensors such as Melanoma Differentiation Associated gene 5 (MDA5), encoded by the IFIH1 gene. MDA5 has been shown to be involved in pro-inflammatory and immunoregulatory outcomes, thus determining the response of pancreatic islets to viral infections. Although the function of MDA5 has been previously well explored, a detailed immunohistochemical characterization of MDA5 in pancreatic tissues of non-diabetic and T1D donors is still missing. In the present study we used multiplex immunofluorescence imaging analysis to characterize MDA5 expression and distribution in pancreatic tissues obtained from 22 organ donors (10 non-diabetic autoantibody-negative, 2 non-diabetic autoantibody-positive, 8 recent-onset and 2 long-standing T1D). In non-diabetic control donors, MDA5 was expressed both in α- and in β-cells. The colocalization rate imaging analysis showed that MDA5 was preferentially expressed in α-cells. In T1D donors, we observed an increased colocalization rate MDA5-glucagon respect to MDA5-insulin in comparison to non-diabetic controls; such increase was more pronounced in recent-onset respect to long-standing T1D donors. Of note, an increased colocalization rate MDA5-glucagon was found in insulin-deficient-islets (IDI) respect to insulin-containing-islets (ICI). Strikingly, we detected the presence of MDA5-positive/hormone-negative endocrine islet-like clusters in T1D donors, presumably due to dedifferentiation or neogenesis phenomena. These clusters were identified exclusively in donors with recent disease onset and not in autoantibody-positive non-diabetic donors or donors with long-standing T1D. In conclusion, we showed that MDA5 is preferentially expressed in α-cells and its expression is increased in recent-onset T1D donors. Finally, we observed that MDA5 may also characterize the phenotype of dedifferentiated or newly forming islet cells, thus opening to novel roles for MDA5 in pancreatic endocrine cells.